Reverse Factoring, Environmental Subsidies, and Investment Returns: Panel Evidence from European Logistics Firms - Makhmudov, Samariddin; Matyakubova, Aziza; Kulmanov, Toshmurod; Kurbanov, Mukhiddin; Nazarova, Gulchekhra; Turanboyev, Boburjon; Achilova, Komila (International Journal of Economics and Financial Issues, 2025)
This article evaluates the drivers of investment performance in European logistics, with a focus on the dimensions of supply chain financing and sustainability incentives. Using annual data provided by the Moody’s Orbis (Bureau van Dijk) database, 24 logistics companies in Continental Europe from 2013 to 2024 were analyzed to examine how each of the reverse factoring, environmental subsidies, inventory financing, and liquidity condition affect investment efficiency. Firm performance is measured by return on investment, profit margin, and cost savings. The analysis uses pooled OLS, fixed and random effects panel regression to account for heterogeneity across firms and time. Results indicate that reverse factoring improves the return on investment, highlighting it is important for financial flexibility in logistics. In contrast, inventory financing negatively affects all three of performance measures which reflects collateral borrowing risks. Environmental subsidies have a moderate positive effect, while no cash ratio has a statistically significant effect on performance. The findings as a whole underscore how policies and financing strategies play in investment performance, which will be of use to both corporate operating managers and policy makers.